Melioidosis - A Rare Infectious Disease with Atypical Presentation (Bangladesh Journal of Otorhinolaryngology, 2015)
Melioidosis is an infectious disease caused by a Gram negative bacterium, Burkholderia Pseudomallei. It is endemic in parts of Southeast Asia, Taiwan & northern Australia. In Bangladesh it is rare. Laboratory identification of B. pseudomallei can be difficult, especially where it is rarely seen. The disease is of public health importance as it is associated with high fatality rate in human being. The disease is known as a remarkable imitator due to the wide & variable clinical spectrum of its manifestations. Septicaemia, sepsis, septic arthritis, lung nodules & pneumonia are well recognized manifestations of Melioidosis. ENT manifestation is rare. Here we reported a case of mallioidosis. The patient was diabetic hailing from Gazipur, presented with cellulitis over the neck and septic arthritis of left shoulder and hip with lung nodules. He responded to prolonged treatment with intravenous ceftazidime. DOI: http://dx.doi.org/10.3329/bjo.v20i1.22157 Bangladesh J Otorhinolaryngol; April 2014; 20(1): 46-49